Buying to Blunt Negative Feelings: Materialistic Escape from the Self. Issue 3 (September 2016) - Donnelly, Grant E.; Ksendzova, Masha; Howell, Ryan T.; Vohs, Kathleen D.; Baumeister, Roy F.
We propose that escape theory, which describes how individuals seek to free themselves from aversive states of self-awareness, helps explain key patterns of materialistic people's behavior. As predicted by escape theory, materialistic individuals may feel dissatisfied with their standard of living, cope with failed expectations and life stressors less effectively than others, suffer from aversive self-awareness, and experience negative emotions as a result. To cope with negative, self-directed emotions, materialistic people may enter a narrow, cognitively deconstructed mindset in order to temporarily blunt the capacity for self-reflection. Cognitive narrowing decreases inhibitions thereby engendering impulsivity, passivity, irrational thought, and disinhibited behaviors, including maladaptive consumption.